Secret service : hidden systems that deliver unforgettable customer service - DiJulius, John R., 1964- (AMACOM, 2003)
The new rules for persuasive messaging. When it comes to messaging, what worked in the past won't work today. Our noisy, digital world has undermined our ability to focus. For a message to grab attention and persuade, it now has to pass the SAUCE test and be: Simple, Appealing, Unexpected, Credible, and Emotional. Secret Sauce shows you how to transform unconvincing messages into compelling copy. It comes with a 15-question SAUCE test and a Heat Gauge which allows you to precisely measure the persuasive impact of your messages. Short, easy to read, and packed with visuals, Secret Sauce provides: Clear examples of what works and what doesn't * Fascinating insights from behavioral and neurological research * Powerful lessons from successful and failed campaigns Less than 10 percent of marketing messages are truly compelling-engaging the head and heart. Secret Sauce helps you weed out the clutter and craft messages that stick.